Economic Interpretation of Philosophy of Bhagavad Gita: A Descriptive Analysis - Pandey, Yuba Raj (Economic Journal of Development Issues, 2018)
Bhagavad Gita has proposed number of economic principles and values. In his recent book, The Idea of Justice, Amartya Sen discusses main massage of the Bhagavat Gita that is ‘duty is important’. In addition to this, the central thesis of the Gita from the philosophical view is found through the concept of yoga. The path of action without motive (or the path of Niskam Karma Yoga) is the most important of those various principles. The path of knowledge (Gyan Yoga) and the path of commitment to work (Bhakti Yoga) are other important principles. Bhagavad Gita analyses in detail the behavioral nature of different individuals and the result of the behavior of the individual. It emphasizes on the good moral character and considers labour as the duty of each and every individual. Similarly it describes about the qualities of life and the happiness of people. Self-reliance of the individual is also emphasized in the Bhagavad Gita. Full commitment to fulfill ones assigned task makes the task successfully accomplished even if people do not care about the fruit (returns from it) before doing the task. Doubts and continuous eye in the fruit work may divert the attention of the actor from the work to the fruit only. Full concentration in the work is necessary to make the work fully successful. The concepts of sustainable development and human development also have their roots in the Bhagavad Gita. Economic Journal of Development Issues Vol. 23&24 No. 1-2, (2017) Combined Issue, Page : 77-101